Understanding the link between graduate experiences and workforce integration in physical education and sports science - Nozaleda, Bryan M.; Saquing, Jasmin B.; Dayag-Tungpalan, Maricel L.; Arao, Hans Freyzer B.; Ramos, Chita C.; Casauay, Daniel T. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Graduate employability remains a critical challenge in higher education in fields with diverse career pathways like physical education and sports science (PESS). Despite efforts to enhance employability through curriculum improvements and institutional support, gaps persist in workforce integration, particularly for non-teaching graduates. This study investigates the relationship between higher education experiences and employment outcomes among PESS graduates. Using data from 274 alumni of a state university in the Philippines, the study employed binary logistic regression to assess the influence of specialization, postgraduate education, and institutional support on employability. Results indicate that graduates in the teaching track were significantly more likely to secure employment as professional educators, while non-teaching graduates faced challenges aligning their careers with their academic background. Enrollment in postgraduate education emerged as a strong predictor of employment, however, curriculum evaluation and overall university experience were not immediate predictors of employability, though long-term employment outcomes were positively associated with graduates’ perceptions of their academic training. These findings reinforce the need for higher education institutions (HEIs) to strengthen career development initiatives for non-teaching graduates and enhance work-integrated learning (WIL) opportunities.